THE BEETLES (INSECTA, COLEPTERA) FAUNA OF KATON-KARAGAY STATE NATIONAL NATURЕ PARK (SOUTH-WESTERN ALTAY, EAST KAZAKHSTAN). - A.U. Gabdullina (Acta Biologica Sibirica, 2016)
A review of the fauna beetles from Katon-Karagai National Park in East Kazakhstan (Southwest Altai) is presented: 725 species (of 351 genera and 45 families). Some two species - Carabus imperialis и Carabus michailovi are listed in to the Republic Kazakhstan Red Data Book, one species Cucujus cinnaberinus is listed in the Red List of the International Union of Nature Conservation (IUCN).